The mannan of Candida albicans lacking β-1, 2-linked oligomannosides increases the production of inflammatory cytokines by dendritic cells. (May 2013) - Ueno, Keigo; Okawara, Akiko; Yamagoe, Satoshi; Naka, Takashi; Umeyama, Takashi; Utena-Abe, Yuki; Tarumoto, Norihito; Niimi, Masakazu; Ohno, Hideaki; Doe, Matsumi; Fujiwara, Nagatoshi; Kinjo, Yuki; et al.
<x xml:space="preserve">Abstract</x> Mannans are mannose polymers attached to cell wall proteins in all Candida species, including the pathogenic fungus Candida albicans. Mannans are sensed by pattern recognition receptors expressed on innate immune cells. However, the detailed structural patterns affecting immune sensing are not fully understood because mannans have a complex structure that includes α- and β-mannosyl linkages. In this study, we focused on the β-1, 2-mannosides of N-linked mannan in C. albicans because this moiety is not present in the non-pathogenic yeast Saccharomyces cerevisiae. To investigate the impact of β-1, 2-mannosides on immune sensing, we constructed a C. albicans ∆mnn4/∆bmt1 double deletant. Thin-layer chromatography and nuclear magnetic resonance analyses revealed that the deletant lacked β-1, 2-mannosides in N-linked mannan. Mannans lacking the β-1, 2-mannosides induced the production of higher levels of inflammatory cytokines, including IL-6, IL-12p40 and TNF-α, in mice dendritic cells compared to wild-type mannan. Our data show that β-1, 2-mannosides in N-linked mannan reduce the production of inflammatory cytokines by dendritic cells.